Friedman Tongue Position with the Obstructive Sleep Apnea Syndrome (OSAS) Correlation on Patient with Ischemic Stroke - Yuniarti Yuniarti; Alya Tursina; Shenny Dianathasari Santoso; Ahda Febiyanti; Putri Adinie Esca Nissa (Universitas Islam Bandung, 2019)
Stroke is the number one cause of disability in the world. Sleep disturbances exacerbate post-stroke disabilities in addition to physical disorders. Sleep disorder breathing (SDB), especially obstructive sleep apnea syndrome (OSAS) is the most commonly found in stroke patients (more than 50%). Sleep disorders in patients with ischemic stroke may occur because of obstruction in the upper airway. To facilitate the assessment of the upper airway, Friedman set up a standard naso-velo-oropharyngeal examination area. There are four degrees of Friedman tongue position. This check can predict the presence or absence of OSAS. Obstructive sleep apnea syndrome can be assessed using STOP-BANG questionnaire, an instrument designed to rapidly detect obstructive sleep apnea (OSA) disorder, with an indication of score 5–8 is high-risk, 3–4 is moderate-risk, and 0–2 is low-risk. The method of this study was observational with cross-sectional design in acute phase ischemic stroke patient based on head CT-scan in RSAU dr. M. Salamun Bandung from August–December 2016. Statistical analysis using non-parametric Kruskal-Wallis test and Spearman's rank correlation test. The total subjects of this study were 38 people. The results showed that there was a significant relationship between Friedman tongue position and OSAS in stroke patients at RSAU dr. M. Salamun with p value=0.007. In conclusion, the tongue is an important anatomical structure in OSA patients, so evaluation of the position of the tongue is important to predict the severity of OSA. HUBUNGAN DERAJAT FRIEDMAN TONGUE POSITION DENGAN KEJADIAN OBSTRUCTIVE SLEEP APNEA SYNDROME (OSAS) PADA PENDERITA STROK ISKEMIKStrok merupakan penyebab disabilitas nomor satu di dunia. Disabilitas pascastrok selain gangguan fisik diperburuk dengan gangguan tidur. Sleep disorder breathing (SDB) terutama obstructive sleep apnea syndrome (OSAS) paling sering ditemukan pada pasien strok (lebih dari 50%). Gangguan tidur pada penderita strok iskemik dapat terjadi karena obstruksi pada saluran napas atas. Untuk memudahkan penilaian saluran napas atas, Friedman membuat standar pemeriksaan daerah naso-velo-orofaring. Terdapat empat derajat Friedman tongue position. Pemeriksaan ini dapat memprediksi ada tidaknya OSAS. Obstructive sleep apnea syndrome dapat dinilai menggunakan STOP-BANG questionnaire, suatu instrumen yang dibuat untuk dapat secara cepat mendeteksi obstructive sleep apnea (OSA), dengan indikasi skor 5–8 risiko tinggi, 3–4 risiko sedang, dan 0–2 risiko rendah. Metode penelitian ini adalah observasional dengan rancangan cross-sectional pada pasien strok iskemik fase akut berdasar atas hasil CT-scan kepala di RSAU dr. M. Salamun pada Agustus–Desember 2016. Analisis statistik menggunakan uji nonparametrik Kruskal-Wallis dan uji korelasi rank Spearman’s. Total subjek penelitian 38 orang. Hasil penelitian menunjukkan bahwa terdapat hubungan bermakna antara derajat Friedman tongue position dan kejadian OSAS pada pasien strok di RSAU dr. M. Salamun dengan nilai p=0,007. Simpulan, lidah merupakan struktur anatomi yang penting pada pasien OSA sehingga evaluasi posisi lidah penting untuk memprediksi tingkat keparahan OSA.